2012
DOI: 10.1155/2012/975407
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Evaluate the Benefits of Casing Treatment in Axial Compressors

Abstract: Passive control devices based on casing treatments have already shown their capability to improve the flow stability in axial compressors. However, their optimization remains complex due to a partial understanding of the related physical mechanisms. In order to quantitatively assess the interaction between slots and the blade tip flow, the present paper develops a novel analysis methodology based on a control-volume approach located in the rotor tip region. This methodology may be used for analyzing the casing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The separated area, which is measured by the distance of the separated line from the TE, is relatively less for GD ¼ 3% and 5% and for U* ¼ 0. 35. This implies that the stall is delayed in these two cases, which is responsible for the high performance of the turbine.…”
Section: Internal Flow Analysismentioning
confidence: 99%
“…The separated area, which is measured by the distance of the separated line from the TE, is relatively less for GD ¼ 3% and 5% and for U* ¼ 0. 35. This implies that the stall is delayed in these two cases, which is responsible for the high performance of the turbine.…”
Section: Internal Flow Analysismentioning
confidence: 99%
“…Legras et al [13] and Chen et al [14] investigated the effect of multiple square grooves on the stable operating range of a transonic compressor through experiments and numerical simulations. Chen et al [14] showed that the elimination of the reversed flow structure on the rotor tip correlated with the axial momentum delivered by the square grooves.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2014) verified the ability of unmatched grid approaches in simulation of the casing treatment and showed that circumferential grooves could reduce the backward axial momentum flux in the gap flow and accordingly extend the stall margin of the compressor. Legras et al (2012) presented a generalized method of Shabbir's approach to reveal the flow mechanisms induced by any CT geometry. Their results indicate that the axisymmetric CT is characterized by its bleeding effect and the slot-type CT is characterized by both a bleeding effect at the rear-part and the blowing effect at the front-part of the compressor.…”
Section: Introductionmentioning
confidence: 99%